1995
DOI: 10.1152/jn.1995.74.1.322
|View full text |Cite
|
Sign up to set email alerts
|

Discharge patterns of hippocampal theta-related cells in the caudal diencephalon of the urethan-anesthetized rat

Abstract: 1. Single-unit discharge patterns of cells in specific nuclei of the caudal diencephalon were characterized in relation to simultaneously recorded field activity from the stratum moleculare of the dentate gyrus according to the criteria that have been used previously to classify cells in the hippocampal formation (including entorhinal cortex), medial septum, and cingulate cortex. Theta (theta)-related cells were classified as 1) tonic theta-ON, if they discharged nonrhythmically and increased their discharge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
1
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 33 publications
6
94
1
2
Order By: Relevance
“…It seems likely, therefore, that, as has been suggested previously, rhythmical activity in SuM is not necessary for the expression of per se (Kirk and McNaughton, 1993;Bland et al, 1995;Thinschmidt et al, 1995). Further, it has been demonstrated that lesions of the RPO produced little obvious change in hippocampal in freely moving animals (Farris and Sainsbury, 1990).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It seems likely, therefore, that, as has been suggested previously, rhythmical activity in SuM is not necessary for the expression of per se (Kirk and McNaughton, 1993;Bland et al, 1995;Thinschmidt et al, 1995). Further, it has been demonstrated that lesions of the RPO produced little obvious change in hippocampal in freely moving animals (Farris and Sainsbury, 1990).…”
Section: Discussionmentioning
confidence: 60%
“…It has been suggested McNaughton, 1991, 1993) that the level of ascending tonic RPO input is transduced into the frequency of in the SuM (reflected in the frequency of SuM cell burst discharge), and that this frequency-coded information is then fed via the medial forebrain bundle (Veazy et al, 1982;Vertes, 1992) to the MS/vDBB. The PH, however, may provide tonic input (possibly cholinergic; see Brazhnik and Vinogradova, 1986;Oddie et al, 1994;Bland et al, 1995) to the MS/vDBB and hippocampus that accentuates rhythmic firing in septal cells (Brazhnik and Vinogradova, 1986;Bland et al, 1994) and is required for the expression of field activity in the hippocampus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior hypothalamic nucleus has been linked to several functions including cardiovascular activity, respiration, locomotion, wakefulnessiarousal, antinociception, and recently the modulation of the hippocampal EEG (Shik and Orlovsky, 1976;Buccafusco and Brezenoff, 1979;Eldridge et al, 1981Eldridge et al, , 1985Carstens, 1982;Ohta et al, 1985;DiMicco et al, 1986;DiMicco and Abshire, 1987;Mori, 1987;Martin et al, 1988;Waldrop et al, 1988;Wible et al, 1988;Lin et al, 1989;Pare et al, 1989;Spencer et al, 1990;Sinnamon, 1993;Bland et al, , 1995Vertes et al, 1995). The PH has been viewed as an important center for the integration of these various activities.…”
Section: General Functional Considerationsmentioning
confidence: 99%